Pemberdayaan Ekonomi Melalui Akad Qardul Hasan Pada KSU BMT Al-Mawaddah Bangsalsari Jember Berdasarkan Fatwa DSN-MUI No.19/DSN-MUI/IV/2001 - Syafii, Muhammad; Herliandis, Dimas (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2023)
Microeconomic empowerment is a program carried out by the central government to local governments. The existence of MSMEs in each region is experiencing rapid development, but this is not matched by the existence of adequate capital, or the lack of financial institutions that can support the existence of MSMEs. Therefore, an Islamic microfinance institution named the Baitul Maal Wat At-Tamwil institution emerged with one of the MSME development products, namely the Qardul Hasan contract (financing agreement without excess funds in return) and BMT Al-Mawaddah, Bangsalsari sub-district, which is one of the sharia financial institutions that have Qardul Hasan products. The formulation of the problem seeks to explain the application of the Qardul Hasan product and the conformity of the product with existing regulations. This type of qualitative research with data collection techniques using observation, interviews and documentation, the data collected was analyzed by descriptive method and the validity of the data using the method of persistence and constancy of observation. The results of the study explained that the Qardul Hasan contract at BMT Al-Mawaddah was running in accordance with the DSN-MUI Fatwa rules No.19/DSN-MUI/IV/2001, but it was not optimal for the object of Qardul Hasan's product recipients in developing the MSME sector. Because the recipients of the Qardul Hasan product contract are still minimal and have not spread personally. Suggestions for institutions are to maximize product recipients and apply sanctions so that there is an educational effect for members and institutional assets can rotate optimally.